PENGARUH PELATIHAN, BUDAYA ORGANISASI, DAN LINGKUNGAN KERJA TERHADAP PRODUKTIVITAS KERJA PEGAWAI DI KANTOR PELAYANAN PAJAK PRATAMA BANGKALAN - Nur Lailly; Sundjoto; Sri Rahayu (MANAJEMEN DEWANTARA, 2023)
This study aims to examine the effect of training, organizational culture, and work environment on employee productivity at work. The sample in this study were 79 employees at the Bangkalan Tax Service Office. The analytical tool used is multiple linear regression. The data processing application uses SPSS version 20. The results show that simultaneously by using the F test, the variables between training, organizational culture, and work environment affect employee work productivity, while partially by using the t test, training variables, organizational culture, and work environment has a significant effect on employee work productivity at KPP Pratama Bangkalan